The Impact of Collaborative Learning on Teachers’ Pedagogical Skills and Instructional Practices - Ahmad, Razzaq; Muhammad Ehsan; Saeed Khan (JCTE, 2025)
Collaborative learning is a teaching and learning approach in which groups of students work together to solve problems, finish tasks, or produce a product. The focus of the present study was to investigate the impact of collaborative learning on teachers’ pedagogical skills and instructional practices among primary school teachers. Primary school teachers who are receiving Continuing Professional Development Training for the session 2024-25 under the Directorate of Professional Development Peshawar were the population of the study. Random sampling technique was used for this study. The sample of the study was 100 Primary School teachers of three CPD Centers in Lahor (Swabi). A 5 Point Likert scale questionnaire was used for data collection. The data was analyzed through SPSS using descriptive statistics, correlation analysis and regression analysis. The findings reflected the importance of structured collaborative learning programs within educational institutions. The role of peer learning was highlighted in teacher development and demonstrates the value of institutional support for collaborative initiatives. The research also extends existing knowledge on professional development frameworks, providing empirical support for social learning theories in teacher education. It was recommended that active participation in collaborative learning communities, the documentation and sharing of successful teaching practices, regular peer observation and feedback, and the maintenance of reflective journals to track professional growth for teachers.